Household choice of public versus private health institution for maternal health-care: A case study of Bahawalpur (Pakistan) - Rana Ejaz Ali Khan; Sara Noreen (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
In Pakistan the ratio of institutional delivery that is one of the most important components of maternal health-care is lower than in a number of developing economies. The ratio of public sector institutional delivery is again lower than private sector institutional delivery. Government of Pakistan spends a lot of money for health services and there is a complete system of health-care comprising of basic health units to bigger hospitals in the country. For policy making it is necessary to analyze why the households choose private sector health institutions. The paper empirically analyzes the determinants of choice of public versus private sector health institution by the household. For the purpose binary logistic regression (bivariate and multivariate) has been applied on primary data collected form Bahawalpur. The results have shown that birth-interval, woman education, partner's education, woman autonomy (freedom of movement), planned pregnancy, media exposure, wealth index, birth-interval, number of pregnancies and pregnancy complications decreases the probability of delivery at public sector health institution. The inter-spouse age gap, woman work status and health worker' visit enhance the likelihood of delivery at public sector health institution. It may be concluded that quality of health-care matters for choice of private sector health institutions and private sector health institutions are substitute to public sector health institutions. The public sector institutions should increase the quality of health-care and there should be a regulatory body for ranking the health institutions.
Keywords: 330; maternal health; natal-care; health economics; household economics; household decision-making; woman autonomy; public sector health institutions; private health institutions